تقييم فعالية السياسة النقدية في الجزائرباستخدام نموذج تصحيح الخطأ العشوائي(vecm) - Ayache, Zoubeir (Finance and Business Economies Review, 2018)
The objective of this research paper is to try to evaluate the effectiveness of monetary policy on economic growth and inflation in Algeria, using the Vector Error Correction Model (VECM ) and quarterly data covering the first trimester from 1990 to the fourth trimester from 2016 , which relates to the following variables: the rate ofGrowth of the monetary mass, inflation rate and the rate of growth of gross domestic product. The results of the response Functions analysis indicated that a random shock in therate of growth of monetary mass by one standard deviation would always have a positive effect onrate of growth of gross domestic product (GDP). in contrast, a random shock in therate of growth of monetary mass by one standard deviation would have a positive effect on inflation rate in the short term and the impact of the shock would then fade in the medium term and then turn negative in the long term, the study also showed that monetary policy has a great effect on the macro economy in Algeria.